2015
DOI: 10.1021/acs.est.5b01233
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Metabolism of Phthalate Esters by Edible Plants

Abstract: Phthalate esters (PAEs) are large-volume chemicals and are found ubiquitously in soil as a result of widespread plasticulture and waste disposal. Food plants such as vegetables may take up and accumulate PAEs from soil, potentially imposing human health risks through dietary intake. In this study, we carried out a cultivation study using lettuce, strawberry, and carrot plants to determine the potential of plant uptake, translocation, and metabolism of di-n-butyl phthalate (DnBP) and di(2-ethylhexyl) phthalate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(83 citation statements)
references
References 45 publications
2
81
0
Order By: Relevance
“…For maize and wheat tissues, especially grains, their BCFs with respect to PAE congeners are far greater than one, indicating the strong PAE enrichment abilities of maize and wheat. The BCFs of PAE congeners in both whole maize and wheat plants are equal to those of herbaceous plants52, but obviously higher than those of vegetables in previous studies8171820, implying the higher PAE enrichment ability of maize and wheat than vegetables.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…For maize and wheat tissues, especially grains, their BCFs with respect to PAE congeners are far greater than one, indicating the strong PAE enrichment abilities of maize and wheat. The BCFs of PAE congeners in both whole maize and wheat plants are equal to those of herbaceous plants52, but obviously higher than those of vegetables in previous studies8171820, implying the higher PAE enrichment ability of maize and wheat than vegetables.…”
Section: Resultsmentioning
confidence: 67%
“…Dietary intake from contaminated food is the primary source of PAE exposure in the general population15; according to the model of the European Union System for the Evaluation of Substances (EUSES), the exposure to edible crops can account for 89.9% and 51.0% of the total human intake exposure for dibutyl phthalate (DBP) and DEHP, respectively16. Previous studies reported the occurrence and status of PAEs in the soil-crop system and showed that the accumulations of PAEs in plant tissues are mainly govern by combined factors of organic matter, minerals, pH, temperature and microorganisms of soils and intrinsic physicochemical properties of pollutants81718192021. However, most of these studies were conducted in vegetable crop fields, whereas the dynamics of PAEs in soil–cereal crop systems, particularly the cereal cropping system from actual agricultural fields, remains unclear.…”
mentioning
confidence: 99%
“…The root-water concentration factor (RWCF, Equation 3) and root-soil concentration factor (RSCF, Equation 4) were calculated as the PAEs level in root to that in water and soil, respectively. The translocation factor (TF, Equation (5)) was calculated as the ratio of PAEs level in leaves to that in roots [6].…”
Section: Discussionmentioning
confidence: 99%
“…As additives in numerous products, including coatings, coverings, insecticides, flooring, drainpipes, packaging, cosmetics, adhesives, and paints [2], they may migrate into the environment via various pathways including microbial transformation, microsomal metabolism, and sunlight exposure [3]. With strong chemical bond to the matrices of polymers, PAEs are persistent and found in almost all the environments, such as rivers [4], sediments [5], soils [6], sewage [7], air [8], biota [9], and even in human tissue [10]. Many pieces of evidence show the carcinogenic, teratogenic, and estrogenic effects of PAEs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic organisms can also contribute to the metabolism of organic chemicals within plants [21]. Plant biotransformation rates are available for a few pesticides [17,22,23], pharmaceutical chemicals [24], and plasticizers [25,26]. Furthermore, plant dissipation rates (degradation and transport loss mechanisms) can vary considerably between different plant compartments and environmental conditions [27,28].…”
Section: Introductionmentioning
confidence: 99%